2017
DOI: 10.30979/rev.abeno.v17i1.358
|View full text |Cite
|
Sign up to set email alerts
|

E-learning em Diagnóstico Bucal: relato de experiência na Universidade de Brasília

Abstract: RESUMODefine-se e-learning como qualquer tipo de situação educacional em que o conteúdo é disponibilizado eletronicamente via Internet quando e onde as pessoas precisam. Usando as possibilidades que o ambiente virtual oferece para o ensino, foi elaborado um e-módulo na Plataforma Moodle. O objetivo desse estudo foi verificar o acesso, desempenho e aceitação de estudantes de graduação em Odontologia frente à utilização do e-módulo nas atividades online da Disciplina de Diagnóstico Bucal na Universidade de Brasí… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…The current generation has more access and ease to use computers and other electronic devices for communication and quick searches. Nevertheless, it is observed that they still need rewards, such as the addition of notes to use these devices, so they can employ them as tools for learning 8,16 . As can be seen in classes A and B, the means for the face-to-face interpretation scores of Groups A1 and B1 (who performed the virtual activity before the face-to-face) were higher than in A2 and B2, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current generation has more access and ease to use computers and other electronic devices for communication and quick searches. Nevertheless, it is observed that they still need rewards, such as the addition of notes to use these devices, so they can employ them as tools for learning 8,16 . As can be seen in classes A and B, the means for the face-to-face interpretation scores of Groups A1 and B1 (who performed the virtual activity before the face-to-face) were higher than in A2 and B2, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This system generates educational learning environments, which are known as elearning, learning management systems (LMS), or VLEs. The incorporation of Information and Communication Technologies (ICTs) for the educational scenario has enabled the reevaluation of the way education is practiced, establishing a new paradigm for teaching and learning 4,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Além da possibilidade de ser adicionadas diversas mídias (textos, imagens, vídeos ou animações digitais) (ALENCAR; PEREIRA; ANDRADE, 2017; MARTINS; ZERBINI, 2016). Inúmeras plataformas educacionais podem ser utilizadas na EaD como o Modular Object Oriented Dynamic Learning Environment (MOODLE)(MATSUBARA et al, 2016;FEITOSA, 2016). O MOODLE apresenta como benefícios a possibilidade de disponibilizar materiais didáticos, aulas, atividades, animações, vídeos.…”
unclassified